Pola Produksi, Distribusi Dan Analisi Titik Impas Industri Arang Tempurung Kelapa Di Kawasan Suburban Indonesia - Pitri Yandri (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2014)
Suburb is characterized by two activities at once: residential area and trade and agricultural activities and/or small-scale industries. One of industry exist in the middle of neighborhood is coconut shell charcoal industries. Five manufacturerswere observed to identify and analyze the patterns of production, distribution and production effectiveness. The observation result shows that the entire manufacturer relying on traditional markets in South Tangerang Municipality, Parung District and South Jakarta as a major supplier of raw materials. The main constraints faced by the industries in obtaining raw materials are competition among them (asymmetric information). The pattern of distribution is directly and indirectly distribution. Direct distribution patterns made by selling charcoal to the end consumer (restaurant) and indirect distribution patterns performed by using large suppliers and retailers in traditional markets. The distribution pattern is also performed passively in which the industries are waiting for consumer to come and then make a transaction. However, the entire industries have the effectiveness of production.